2017
DOI: 10.3390/en10040567
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Flow Analysis of a Simple LTD (Low-Temperature-Differential) Heat Engine

Abstract: A combined thermal and flow analysis was carried out to study the behavior and performance of a simple, commercial LTD (low-temperature-differential) heat engine. Laminar-flow solutions for annulus and channel flows were employed to estimate the viscous drags on the piston and the displacer, and the pressure difference across the displacer. Temperature correction factors were introduced in the thermal analysis to account for the departures from the ideal heat transfer processes. The flow analysis results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The source of power of the Stirling engine is the pressure gradient in air room, which is formed because of the difference in the temperature of the cold and hot plates. In this section, we refer to the method of Kim et al to calculate the gas work of the Stirling engine [8]. Because of the low speed and small size of the gamma-type Stirling engine, the airflow in the air room can be reasonably assumed to be laminar.…”
Section: Gas Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of power of the Stirling engine is the pressure gradient in air room, which is formed because of the difference in the temperature of the cold and hot plates. In this section, we refer to the method of Kim et al to calculate the gas work of the Stirling engine [8]. Because of the low speed and small size of the gamma-type Stirling engine, the airflow in the air room can be reasonably assumed to be laminar.…”
Section: Gas Workmentioning
confidence: 99%
“…However, a variety of instantaneous pressures should be considered in reality. Kim et al used thermal flow to analyze high and low pressures in an LTD Stirling engine [8].…”
Section: Introductionmentioning
confidence: 99%
“…10 Their research focused on the use of large-scale thermoelectric refrigerator for the air conditioning applications. Kim et al 11 suggested a combined thermal-flow analysis of a simple low-temperature-differential (LTD) heat engine to utilize lowgrade waste heat from the industries. In harvesting mechanical energy from the waste heat, Sato et al 12 demonstrated a functional shape memory alloy (SMA) heat engine that produced 1.16 W of electrical power at a temperature of 100°C.…”
Section: Introductionmentioning
confidence: 99%
“…Stirling engines have high theoretical efficiencies and can be powered by external heat sources; therefore, there is a high degree of potential for Stirling engines to produce renewable energy from several sustainable sources, such as concentrated solar thermal power and biomass. Theoretically, Stirling engines can convert heat into mechanical energy at the Carnot efficiency [1,2], which is the maximum achievable efficiency for heat engines, but in practice Stirling engines have failed to achieve these high efficiencies and the reduction is more than would be predicted by typical mechanical losses alone [3]. The practical efficiency depends on many factors, including the operating conditions, regenerator effectiveness [4], friction losses [5,6], dead volume [7], and the ability of the engine to follow the theoretical Stirling cycle.…”
Section: Introductionmentioning
confidence: 99%